Sensitivity analysis of reservoir and rock properties during low salinity water injection - Afshin Davarpanah; Behnam Mirshekari (Energy Reports, 2019)
The ubiquitous consumption of hydrocarbon fuels in a vast majority of industrial purposes has been dramatically increased in the coming decades. Therefore, the reason why numerous studies experimental investigations are being done is to enhance the oil recovery factor. Low salinity water injection is considered as the significant proposed enhanced oil recovery techniques in which the salinity percentage of the injected water is adjusted to improve oil displacement efficiency. Hence, low salinity water injection is considerably influenced by the oil recovery factor regarding altering wettability condition. The objective of this study is to simulate the low salinity water injection under different reservoir characteristics of rock compressibility, porosity and net to gross (NTG) on the amount of total field oil production (FOPT), total field gas production (FGPT), field pressure ratio (FPR) and field gas-oil ratio (FGOR) for 7400 days . Consequently, rock compressibility has less impact on the amount of total field oil production, total field gas production, field pressure ratio, and field gas-oil ratio. By increasing the amount of porosity and NTG, the amount of FOPT, FGPT, and FGOR are raised dramatically, and it is evident that this parameter is directly influenced by this type of reservoir. On the contrary, the amount of FOPT, FGPT, and FGOR are decreased in the NTG period of 0.5 to 1.
Keywords: 330; Gas production; Oil production; Low salinity water injection; Porosity; Rock compressibility